PERAN KEPEMIMPINAN PEREMPUAN DALAM PERSPEKTIF GENDER - Rahim, Abdul (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2016)
The role of women in society among the aspect of reproduction, economic, social, politic, and Islamic leadership put women as members in community activities or organizations. This is proved by the amount of women who are active in organizations and they aren?t brave enough as well as men. Because of this reason, only few of their proposals are accepted and implemented into the existing political world. The factor influences women's involvement in society is their level of education. All the tasks entrusted to women can be held because of their education. This means that there is relevance between the tasks and education.